2019
DOI: 10.22438/jeb/40/3(si)/sp-13
|View full text |Cite
|
Sign up to set email alerts
|

Determination of environmental effects on production efficiency of agricultural demonstration zones

Abstract: The present study aimed to solve the problems that the production efficiency of national modern development area, and the influence of environment effect on agricultural production efficiency. Based on the input-output data of 51 modern agricultural demonstration zones in Shandong Province in 2015, a three-stage DEA model was used for study. In the first stage, the traditional efficiencies were calculated depended on the original inputs and outputs, and input slacks were evaluated. In the second stage, the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The results show that (1) the National Modern Agricultural Demonstration Zone can enhance agricultural science and technology innovation, and the results remain robust after a series of robustness tests. The findings of this paper are consistent with those of Wu et al (2019), both of which concluded that agricultural demonstration zones can play a policy-driven role in rationalizing the allocation of agricultural production factors and improving agricultural technology. (2) The National Modern Agricultural Demonstration Zone can enhance regional financial capital allocation, financial support for agriculture, and human capital stock, which are the necessary elements for agricultural science and technology innovation, due to policy and financial support.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results show that (1) the National Modern Agricultural Demonstration Zone can enhance agricultural science and technology innovation, and the results remain robust after a series of robustness tests. The findings of this paper are consistent with those of Wu et al (2019), both of which concluded that agricultural demonstration zones can play a policy-driven role in rationalizing the allocation of agricultural production factors and improving agricultural technology. (2) The National Modern Agricultural Demonstration Zone can enhance regional financial capital allocation, financial support for agriculture, and human capital stock, which are the necessary elements for agricultural science and technology innovation, due to policy and financial support.…”
Section: Discussionsupporting
confidence: 88%
“…First, the research object is more precise and valuable. Most of the National Modern Agricultural Demonstration Zone pilots are concentrated at the district and regional levels, and the data used do not provide an accurate picture of the policy effects of the demonstration area (Wu et al, 2019). This paper matches the district, region, and prefecture-level cities targeted by the National Modern Agricultural Demonstration Zone, and the data cover three batches of pilot regions.…”
mentioning
confidence: 99%
“…Fried et al (2002) propose a three‐stage DEA method to avoid these drawbacks by controlling the redundancy caused by the operating conditions. Although the three‐stage DEA model has been popular in the efficiency evaluation of energy industries (Wang, Beusen, et al, 2019; Wang, Sun, & Wang, 2019; Chen et al, 2021) and cultivation practices (Wu et al, 2019), we must recognize that this approach may also produce biased parameters. The reason is that the estimation of each equation is serial rather than simultaneous.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the characteristics that the producers themselves cannot control or change in the short term, these factors are called external environmental factors. According to the research of Wu [ 34 ], Xu [ 35 ], and Xue et al [ 36 ], this paper selects indexes such as smallholders’ agricultural income, education level of smallholders, policy support, and information acquisition as external environment variables.…”
Section: Research Methods and Variables’ Definitionmentioning
confidence: 99%